Jean Rhys twenty-first-century approaches - Johnson, Erica L. 1970-; Moran, Patricia (Edinburgh University Press, 2015)
The 11 newly commissioned essays collected in this volume demonstrate Jean Rhys's centrality to modernism and to postcolonial literature alike by addressing her stories and novels from the 1920s and 1930s, including Voyage in the Dark, Quartet, After Leaving Mr. Mackenzie, and Good Morning, Midnight, as well as her later bestseller, Wide Sargasso Sea (1966). The volume establishes Rhys as a major author with relevance to a number of different critical discourses, and includes a path-breaking section on affect theory that shows how contemporary interest in Rhys correlates with the recent 'affective turn' in the social sciences and humanities. As this collection shows, strangely haunting and deeply unsettling, Rhys's portraits of dispossessed women living in the early and late twentieth-century continue to trouble easy conceptualisations and critical categories